2016
DOI: 10.3389/fnhum.2016.00207
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Uncertainty and Brain Activity Aberrance in the Insula and Anterior Cingulate Cortex Are Associated with Dysfunctional Impulsivity in Borderline Personality Disorder

Abstract: Uncertainty is recognized as an important component in distress, which may elicit impulsive behavior in patients with borderline personality disorder (BPD). These patients are known to be both impulsive and distress intolerant. The present study explored the connection between outcome uncertainty and impulsivity in BPD. The prediction was that cue primes, which provide incomplete information of subsequent target stimuli, led BPD patients to overrate the predictive value of these cues in order to reduce distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Indeed, several studies have shown that self-reported measures of the impulsivity personality trait are associated with “commission errors” in stop-signal, go/no-go, Stroop, and other tasks that require the inhibition of a preponderant response (Enticott et al, 2006; Lansbergen et al, 2007; Saunders et al, 2008; Burle et al, 2016). However, there is also evidence that impulsivity affects action planning in general, that is, not only when a preponderant response ought to be inhibited, both in health (Tzagarakis et al, 2013; Rossi et al, 2018) and in disease (Clark et al, 2006; Kertzman et al, 2010; Mortensen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have shown that self-reported measures of the impulsivity personality trait are associated with “commission errors” in stop-signal, go/no-go, Stroop, and other tasks that require the inhibition of a preponderant response (Enticott et al, 2006; Lansbergen et al, 2007; Saunders et al, 2008; Burle et al, 2016). However, there is also evidence that impulsivity affects action planning in general, that is, not only when a preponderant response ought to be inhibited, both in health (Tzagarakis et al, 2013; Rossi et al, 2018) and in disease (Clark et al, 2006; Kertzman et al, 2010; Mortensen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence is provided by previous fMRI studies using attention tasks, i.e. an emotional Stroop task (Wingenfeld et al 2009) and a Posner task (Mortensen et al 2016), in which BPD patients showed altered attentional control networks (e.g. dACC) compared to NPC.…”
Section: Discussionmentioning
confidence: 90%
“…The functional connectivity was negatively correlated with emotional dysregulation and impulsivity scores, especially with non-planned impulsivity, which relates to self-control and cognitive complexity ( 55 ). The insula has been linked to emotion regulation ( 56 ) and impulsivity ( 57 , 58 ), and is a key component of the salience network which is activated in sensory stimulus-guided goal-directed behaviors ( 59 ). In BPD patients, insula function has been related to emotional processing of pain ( 60 ).…”
Section: Discussionmentioning
confidence: 99%